Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persep - Faris Rahman (Journal of Politic and Government Studies, 2013)
Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Persepsi pengaruh money politic dan Jaringan sosial terhadap Perilaku pemilih pada Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. Kemenangan Pasangan Calon dr. Hj. WIDYA KANDI SUSANTI, MM dan wakilnya H. MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN) MUKH MUSTAMSIKIN, S.Ag, M.SI., (YAKIN)Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010 Studi Kasus Pemilukada kab.Kendal tahun 2010(Faris Faris Faris Nadisa Rahman Nadisa Rahman Nadisa Rahman, , Drs. Turtiantoro, M.Si*Drs. Turtiantoro, M.Si*Drs. Turtiantoro, M.Si* Drs. Turtiantoro, M.Si*Drs. Turtiantoro, M.Si* Drs. Turtiantoro, M.Si*Drs. Turtiantoro, M.Si*Drs. Turtiantoro, M.Si* Drs. Turtiantoro, M.Si*Drs. Turtiantoro, M.Si*Drs. Turtiantoro, M.Si* Drs. Turtiantoro, M.Si* Drs. Turtiantoro, M.Si*, Drs. Susilo utomo, M.SiDrs. Susilo utomo, M.SiDrs. Susilo utomo, M.Si Drs. Susilo utomo, M.SiDrs. Susilo utomo, M.SiDrs. Susilo utomo, M.Si Drs. Susilo utomo, M.Si Drs. Susilo utomo, M.Si )Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas Diponegoro Jurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJurusan Ilmu Pemerintahan, Fakultas Sosial dan Politik, Universitas DiponegoroJl. Jl. Prof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Ko rof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Korof. H. Soedarto, SH, Tembalang, Semarang, Ko de Pos 1269Pos 1269Pos 1269Pos 1269Pos 1269Pos 1269Pos 1269Pos 1269websitewebsite websitewebsitewebsite : http://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.id http://www.fisip.undip.ac.id http://www.fisip.undip.ac.id http://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.id http://www.fisip.undip.ac.id http://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.id http://www.fisip.undip.ac.idhttp://www.fisip.undip.ac.id email: fisip@undip.ac.id email: fisip@undip.ac.id email: fisip@undip.ac.idemail: fisip@undip.ac.id email: fisip@undip.ac.id email: fisip@undip.ac.idemail: fisip@undip.ac.idemail: fisip@undip.ac.idemail: fisip@undip.ac.idemail: fisip@undip.ac.id email: fisip@undip.ac.idemail: fisip@undip.ac.id email: fisip@undip.ac.idemail: fisip@undip.ac.idABSTRACT ABSTRACTABSTRACT ABSTRACTGeneral Election General Election General ElectionGeneral ElectionGeneral Election General Election General Election General Election in accordance in accordancein accordancein accordancein accordancein accordance in accordance in accordance with UU with UU No.32 th 2004 , an electionelection election election to elect a leaderelect a leader elect a leader elect a leaderelect a leaderelect a leader elect a leaderelect a leaderelect a leader in the area in the area in the areain the areain the areain the area directly and directly anddirectly anddirectly and directly anddirectly anddirectly anddirectly and democratically democratically democraticallydemocratically democraticallydemocraticallydemocratically democratically. In the implementation In the implementation In the implementation In the implementation In the implementation In the implementation In the implementation In the implementation In the implementation In the implementation of the election the electionthe election the electionthe election the election of the of theof the couplescouples who often often competecompete compete with winning strategies strategies strategiesstrategiesstrategiesstrategies with a commoncommon common strategy strategy strategystrategy andand not not commonlycommonly commonly commonly used , the use of the use of the use of money politics money politicsmoney politicsmoney politics money politics money politicsmoney politics and theand the and the strategies strategies strategies used by social socialsocial network network partners partners partners in an effort in an effortin an effort in an effortin an effortin an effort in an effort YAKINYAKIN YAKINYAKIN peraihan peraihanperaihanperaihan support, support, althoughalthough although although the use of the use of the use of one of the of theof the ultimate ultimate ultimateultimate strategy strategy of the of theof the candidatescandidatescandidates candidates with the with the YAKINYAKIN YAKINYAKIN using using money politics money politicsmoney politicsmoney politics money politics money politicsmoney politics is a form of is a form ofis a form ofis a form of is a form of is a form of violation violationviolation violation in the administration of in the administration of in the administration ofin the administration of in the administration of in the administration of in the administration of in the administration of in the administration of the the electionelection election election because the because thebecause thebecause the because the reward rewardrewardreward in cash in cashin cashin cash or in kindor in kind or in kind or in kind so as to so as toso as to so as to influence voters influence voters influence votersinfluence votersinfluence voters influence voters andand fade fade values values of of democracy democracy democracydemocracydemocracy in the in the electionelection election electionelection, but in fact in factin fact this strategy this strategy this strategy this strategy this strategythis strategy became becamebecamebecamebecame prevalent prevalentprevalent prevalent becausebecausebecausebecausebecausebecause people people assumeassume assume it it is a necessity necessitynecessitynecessity necessitynecessity or a or aor a compensationcompensation compensation compensation for the support for the supportfor the support for the supportfor the support for the support they provide they providethey providethey providethey provide . While the use ofWhile the use of While the use ofWhile the use ofWhile the use of While the use of While the use ofWhile the use of SocialSocial Social Networking Networking Networking Networking strategy strategy strategystrategy is the is the strategy strategy strategystrategy of winningof winning of winning candidatescandidatescandidates candidates in the elections in the elections in the electionsin the elections in the electionsin the elections by using theby using theby using theby using the by using theby using theby using the network of network of network ofnetwork of relationships relationships relationships , family family familyfamily andand social social relationships relationships relationships relationships that exist that existthat existthat exist within within a societya societya society a societya society its use its use its use by political actors political actors political actorspolitical actorspolitical actors political actorspolitical actorspolitical actors deliberately deliberately deliberately deliberately deliberately deliberatelydeliberately refers to therefers to therefers to the refers to the refers to the refers to the relationships relationships relationships forged forgedforgedforged in order in orderin order in order in order mendapatakan mendapatakan mendapatakan mendapatakan mendapatakan a fringe fringe fringefringe benefit benefit benefit in the form of in the form of in the form of in the form of in the form of material andmaterial andmaterial and material and material and support to systemssystemssystems systemssystems andand political political politicalpoliticalpolitical ideol ogies that are used. that are used. that are used. that are used.In this studyIn this study In this study In this study In this study In this study, researchers used researchers usedresearchers usedresearchers usedresearchers usedresearchers usedresearchers used researchers used researchers used quantitative quantitative quantitative research researchresearchresearchresearch research methodsmethodsmethods research research researchresearch research is used to examine the effect ofexamine the effect ofexamine the effect ofexamine the effect of examine the effect of examine the effect ofexamine the effect of examine the effect ofexamine the effect ofexamine the effect of examine the effect ofexamine the effect of examine the effect of a variablea variablea variable a variable a variable by usingby usingby usingby using by using calculationscalculationscalculations calculationscalculations calculations or statistical tests statistical tests statistical testsstatistical testsstatistical tests statistical tests . LocationsLocations LocationsLocations Locations in the in the study study conductedconducted conductedconducted in the District of in the District of in the District of in the District of in the District of in the District of Kendal Kendal Kendal, precisely , precisely , precisely , precisely , precisely , precisely , precisely , precisely , precisely in the in the District District District BojaBoja , Kendal Kendal Kendal TownTown andand WeleriWeleriWeleri Weleri. The sampling technique The sampling techniqueThe sampling technique The sampling technique The sampling technique The sampling techniqueThe sampling technique The sampling techniqueThe sampling technique in this study using in this study using in this study using in this study using in this study usingin this study usingin this study using in this study using a multia multia multi a multi stage stage random samplingrandom samplingrandom sampling random sampling random sampling random sampling random sampling , which which determined determined determined determined determined the technique the techniquethe techniquethe techniquethe technique the technique of determining of determiningof determining of determiningof determiningof determining of determining a stratified samplea stratified samplea stratified sample a stratified samplea stratified sample a stratified sample a stratified sample a stratified sample a stratified sample a stratified sample, the sample taken sample taken sample takensample takensample taken sample taken through the through thethrough the through the sampling sampling sampling mechanism mechanismmechanismmechanism by takingby takingby takingby taking samples samples samplessamples from the from the from the from the level of level of level of District District District → District District District → VillageVillage Village Village / VillageVillage Village Village ResidentsResidentsResidents → PillarsPillars Pillars Pillars / Neighborhood Neighborhood Neighborhood Neighborhood → KK . In this study this study this study this study the respondents the respondentsthe respondentsthe respondents the respondents the respondents specified specified a number of number ofnumber of 139 respondents respondents respondentsrespondents from the community from the community from the community from the communityfrom the community from the community from the community BojaBoja district district district. Kendal Kendal Kendal TownTown district district district, sub , sub , sub WeleriWeleriWeleri Weleri. The selection of The selection ofThe selection of The selection of The selection of The selection of The selection ofThe selection of respondents respondents respondents based on the primary based on the primary based on the primarybased on the primarybased on the primary based on the primarybased on the primary based on the primarybased on the primary based on the primary based on the primarybased on the primarybased on the primary sampling sampling sampling sampling unit unit so that so that the main the mainthe mainthe main focus focus of this study was of this study wasof this study was of this study was of this study was of this study wasof this study wasof this study was of this study was thethe father father father or head of householdhead of householdhead of householdhead of household head of household head of householdhead of household head of householdhead of household male . Data retrieval Data retrievalData retrievalData retrievalData retrieval Data retrieval Data retrievalData retrieval Data retrieval techniques techniques using primary data primary data primary dataprimary dataprimary dataprimary dataprimary data primary data is through is through is throughis through the distribution ofthe distribution of the distribution ofthe distribution of the distribution of the distribution of the distribution of questionnaires questionnaires questionnaires questionnaires questionnaires as theas the as the primary medium primary medium primary mediumprimary mediumprimary mediumprimary mediumprimary mediumprimary mediumprimary medium of research research researchresearch research outcomes outcomes informnan informnan collectcollect collectcollectcollect. with informants informants while also while alsowhile also using secondary data secondary datasecondary data secondary datasecondary datasecondary datasecondary data secondary data is to is to collect collect collect collect collect collect data data with reference to with reference towith reference towith reference to with reference towith reference towith reference towith reference to written sourceswritten sourceswritten sources written sources written sourceswritten sourceswritten sources as supporting data supporting datasupporting data supporting datasupporting data.